Analysis on Grammatical Error of Students’ English Writing in Descriptive Text at the Tenth Grade of SMA N 8 Kota Jambi Academic Year 2018/2019 - Putri Kurnia; Wennyta Wennyta (JELT: Journal of English Language Teaching, 2019)
This research was done to analyze the grammatical error in writing descriptive text made by tenth grade students in SMA N 8 Kota Jambi Academic year 2018-2019. The method of the research was qualitative method. The sample of the research was tenth grade students of science at SMA N 8 Kota Jambi. Then to get sample of this research, the researcher used random sampling technique. The data was collected by using written test. The finding of the research showed that  tenth grade students of science often make grammatical error in their writing, the error are analyzed based on four types, there are Omission, Addition, Misformation and Misordering. After analyzing the data that got from 37 students, the researcher found out 147 total errors white decide to highest frequency and lowest frequency. The result showed that the highest frequency grammatical error made by students is Omission which 46,93% and the lowest frequency grammatical error made by students isaddition which is 6%. The cause of error in grammatical because learning a foreign language is not the same as learning the mother tongue, it is not the difficulty of the new forms of the language, but mainly by the specific conditions created by customs in native language.Keywords: Analysis, Grammatical Error, Writing, Descriptive Text.